KORBAN DAN PELAKU KEKERASAN FISIK DALAM RUMAH TANGGADI KOTA PEKANBARU - Ermailis Ermailis (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2011)
this paper aim to know the violence factor in the family. In general, victims ofdomestic violenceis awife, while theperpetrators ofviolencearehusbands. Why domenoften become violence? Physicallymenare stronger than women and has invest edinits growth habittousephysical force, other than thatwomenare often economically depen denton her husband